The Influence of Tax Knowledge, Taxpayer Awareness, Income Level, and Tax Sanctions on Motor Vehicle Taxpayer Compliance: A Study at the Mesuji District Samsat Office - Ramadhani, Novita; Maryati (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2026)
This study aims to analyse the effect of taxation understanding, taxpayer awareness, income level, and tax penalties on motor vehicle taxpayer compliance. This study uses a quantitative approach with a survey method. The study was conducted on motor vehicle taxpayers at the Mesuji Regency Samsat Office with a sample size of 100 taxpayers selected using convenience sampling. The data were analysed using multiple linear regression. The results found that, partially, tax understanding, taxpayer awareness and income level had a positive and significant effect on motor vehicle taxpayer compliance, while tax penalties did not have a significant effect on motor vehicle taxpayer compliance. This indicates that the better the taxpayer's understanding, the greater their awareness of the importance of taxes, and the higher their income level, the higher the level of compliance among motor vehicle taxpayers. Meanwhile, the existence of sanctions alone is not enough to encourage compliance among motor vehicle taxpayers. These findings imply that providing education, increasing awareness, and improving the economic conditions of taxpayers play an important role in increasing compliance with motor vehicle tax payments.